Cultural Values of How People Dress in The “Cruella” Movie - Haris, Yusriana; Abdullah, Abdullah; Fitriyani, Fitriyani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This research analysed “Cultural Values of How People Dress in the Cruella Movie”. The analysis of this research focuses on character in the movie. This research aimed to determine the cultural values of how people dress in Cruella movie and the meaning of cultural values of how people dress in Cruella movie. This research used a descriptive qualitative method. The data of this research were obtained from the “Cruella” movie. The data analysis applied using interactive model analysis which includes data reduction, data display, and conclusion (Miles & Huberman, 2014). The results of this research indicated that there were 7 types of cultural values used by character in the Cruella movie namely, intellectual autonomy, affective autonomy, embeddedness, egalitarianism, hierarchy, harmony, and mastery.Keyword: Cultural values, meaning, dress